Exploring Students’ Attitudes on Mobile-Assisted English Learning: A Quantitative Study - Tembe, Harka Raj (The Journal of DMC, 2026)
The integration of mobile phones into educational settings has become increasingly prevalent, particularly in language learning. This study investigates students’ attitudes toward the use of mobile phones in learning English and examines differences in these attitudes based on sex within the context of Nepal. A survey was administered to 80 college students enrolled in bachelor’s and master’s level at Dhankuta Multiple Campus. The Slovin formula was used to determine the sample size, and students were selected using the lottery method. Univariate analysis included frequency counts and percentages, while bivariate analysis employed the Chi-square test to examine attitude differences by sex. Results revealed that students generally held positive attitudes toward mobile-assisted English learning. There was no statistically significant difference between the attitudes of students on the use of mobile phone in learning English on the basis of sex. These results have implications for policymakers, educators, learners, and app developers in promoting mobile learning as a viable supplement to traditional English instruction.